anonymous
  • anonymous
x + y = 6 -x + 3y = -2
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
is there any 2nd euattion
anonymous
  • anonymous
We need a second equation.
anonymous
  • anonymous
to solve it simultaneously

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
The second equation is there, @UditKulka
anonymous
  • anonymous
adding the 2 euations we get
anonymous
  • anonymous
y=1
anonymous
  • anonymous
don't just say it, make her/him see how you did it too
anonymous
  • anonymous
x=1
anonymous
  • anonymous
k
anonymous
  • anonymous
-8x+8x=0
anonymous
  • anonymous
3y-2y=y
anonymous
  • anonymous
-5+6=1
anonymous
  • anonymous
therefore y=1
anonymous
  • anonymous
substituting y in 8x - 2y = 6 we get
anonymous
  • anonymous
8x - 2(1) = 6
anonymous
  • anonymous
6/-2=8x
anonymous
  • anonymous
-3/8=x
anonymous
  • anonymous
i was wrong before but i got it right
anonymous
  • anonymous
cool i have another question n thanks Uditkulka
anonymous
  • anonymous
say them :)
anonymous
  • anonymous
k
anonymous
  • anonymous
x + y = 3 2x - y = 3
anonymous
  • anonymous
Add the equations
anonymous
  • anonymous
y-y=0
anonymous
  • anonymous
x+2x=3x
anonymous
  • anonymous
3x=6
anonymous
  • anonymous
x=6/3
anonymous
  • anonymous
x=2
anonymous
  • anonymous
substitue x in x + y = 3
anonymous
  • anonymous
2 + y =3 y= 3-2 y=1
anonymous
  • anonymous
@9ust_Luv1:Got it ?
anonymous
  • anonymous
wow you r really smart and thanks and i have it yall are a big help
anonymous
  • anonymous
any time!
anonymous
  • anonymous
x + y = 6 -x + 3y = -2
anonymous
  • anonymous
x cancels out
anonymous
  • anonymous
4y=-4
anonymous
  • anonymous
y=-1
anonymous
  • anonymous
x -1 =6 x=6+1 x=7
anonymous
  • anonymous
thanks
anonymous
  • anonymous
last one
anonymous
  • anonymous
x + y = 8 2x = y - 5
anonymous
  • anonymous
take the y on other side
anonymous
  • anonymous
y-y =0
anonymous
  • anonymous
x +2x =3x
anonymous
  • anonymous
3x =3 x=3/3 x=1
anonymous
  • anonymous
1+y =8
anonymous
  • anonymous
8-1
anonymous
  • anonymous
y=7
anonymous
  • anonymous
thanks
anonymous
  • anonymous
k
anonymous
  • anonymous
UditKulka is correct. Using the elimination method then subbing the variable you found back into either of the equations will find the other variable. You can also check your answers by plugging n the variables you solved for into either equation and if they come out equal, then they are correct.
anonymous
  • anonymous
oh okay thanks kelliegirl33
anonymous
  • anonymous
no problem....I didn't really do anything...UditKulka did it all
anonymous
  • anonymous
iik

Looking for something else?

Not the answer you are looking for? Search for more explanations.